Republic of Serbia : Fifth Review Under the Stand-By Arrangement, Request for Modification of End-September Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2010)
The fifth review of Serbia's economic performance under the program supported by a Stand-By Arrangement (SBA) is discussed. It helps in addressing the spillovers from the global financial crisis while establishing a moderate economic recovery. An accelerated pace of structural reforms will help to strengthen medium-term growth and employment prospects, supported by the resumption of adequate capital inflows, in particular through foreign direct investment. A strong commitment to the implementation of structural reforms will strengthen medium-term growth and employment prospects.